Human endometrial stromal cell plasticity: Reversible sFlt1 expression negatively coincides with decidualization - Hanh N. Cottrell; JuanJuan Wu; Bassam H. Rimawi; Juan Manuel Duran; Jessica B. Spencer; Neil Sidell; Augustine Rajakumar (Taylor & Francis Group, 2017)
Preeclampsia (PE) is a major complication of pregnancy in which the placenta is known to have shallow implantation into the uterine decidua. Studies have implicated soluble fms-like tyrosine kinase-1 (sFlt1), a soluble vascular endothelial growth factor (VEGF) receptor protein, in the pathogenesis of PE. sFlt1 has the ability to bind to and neutralize the angiogenic functions of VEGF and placental growth factor (PlGF). The presence of sFlt1 and its action in the endometrium is yet to be determined. We hypothesize that endometrial stromal cells (ESC) at the maternal-fetal interface may play a role in sFlt-1 regulation during pregnancy. In this study, we seek to understand the dynamic regulation of sFlt1 production in primary human ESC as a result of hormone stimulation and withdrawal. To mimic a biphasic menstrual cycle, ESC were treated with cAMP to induce endometrial decidualization that occurs during the luteal secretory phase, followed by cAMP withdrawal reflecting the follicular proliferative phase. Here, we present data to show that (1) ESC produce detectable amounts of sFlt1, (2) sFlt1 expression is turned off during decidualization at both the protein and RNA level (3) ESC decidualization and resulting sFlt1 expression are reversible phenomenon, and (4) Decidualization markers prolactin (PRL) and VEGF expressions in ESC are negatively correlated with sFlt1. These findings may have important implications in diseases such as PE that involve abnormal decidualization, implantation and angiogenesis at the maternal-fetal interface.